The Impact of Mindfulness Meditation on Stress Reduction and Immune Function - Nayla Alator (Professorline, 2025)
This study investigated the effects of Mindfulness-Based Stress Reduction (MBSR) on psychological stress and immune function in healthy adults. In a randomized controlled trial, 68 participants were assigned to either an 8-week MBSR program or an active control condition consisting of health education. Assessments were conducted at baseline, post-intervention, and 3-month follow-up. Outcome measures included psychological questionnaires (Perceived Stress Scale, Depression Anxiety Stress Scales, Five Facet Mindfulness Questionnaire) and immunological parameters (pro-inflammatory cytokines: IL-6, TNF-α, IL-1β; anti-inflammatory cytokine: IL-10; C-reactive protein; natural killer cell activity; T-cell proliferation). Diurnal cortisol patterns were also assessed. Results demonstrated that MBSR participants, compared to controls, showed significant reductions in perceived stress, anxiety, and depression, along with increases in mindfulness facets (all p < 0.001). MBSR also led to significant decreases in pro-inflammatory markers IL-6 (p = 0.002) and TNF-α (p = 0.005), increases in anti-inflammatory IL-10 (p = 0.004), enhanced natural killer cell activity (p = 0.003), and normalized diurnal cortisol patterns (p = 0.002). Many of these effects persisted at the 3-month follow-up. Correlation analyses revealed significant associations between changes in psychological measures, particularly the non-reactivity facet of mindfulness, and changes in immune parameters. These findings suggest that mindfulness meditation may reduce psychological stress and simultaneously modulate immune function through psychoneuroimmunological pathways, potentially offering a complementary approach to stress-related immune disorders and preventive healthcare strategies. Future research should extend these findings to clinical populations and investigate the neurobiological mechanisms underlying these effects.